Risk factors of idiopathic pulmonary fibrosis in Pakistani population: a matched case-control study - Ali Bin Sarwar Zubairi; Rabbani, Unaib; Hassan, Maryam; Fatmi, Zafar; Ahmed, Naseem; Ali, Akbar Shoukat; Rizvi, Nadeem (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the factors associated with idiopathic pulmonary fibrosis risk. Method: The case-control study was conducted from January 5, 2017, to September 4, 2018, at the private-sector Aga Khan University Hospital and the public-sector Jinnah Postgraduate Medical Centre, two large tertiary care centres in Karachi, and comprised adult patients of either gender with diagnosed idiopathic pulmonary fibrosis, as defined by the Indian Chest Registry. Subjects without idiopathic pulmonary fibrosis but registered with the department of pulmonology of the two hospitals were enrolled as controls. Data was collected using a structured questionnaire, and anthropometric measurements were noted for each subject. Gastroesophageal reflux disease was assessed using GerdQ. This was followed by serological evaluations and spirometry. Data was analysed using SPSS 21. Results: Of the 459 subjects, 154(33.6%) were cases and 305(66.4%) were controls. Among the cases, 81(52.6%) were females and 73(47.4%) were males with mean age 66.1±10.9 years. Among the controls, 162(53.1%) were females and 143(46.9%) were males with mean age 64.6±11.1 years (p>0.05.) The most common ethnicity was Urdu-speaking; 89(58%) among the cases and 150(49%) among the controls (p<0.05). Ethnicity, number of persons in the household per room, and type of house were significantly associated with the risk of developing idiopathic pulmonary fibrosis (p<0.05). Conclusion: Ethnicity, type of house and the number of persons in a household per room were found to be the significant risk factors for idiopathic pulmonary fibrosis IPF. Key Words: Idiopathic pulmonary fibrosis, Risk factors, Epidemiology, Pakistan.